Identifikasi dan Analisis Kejadian Penyakit Serta Tingkat Keparahan Penyakit Pada Tanaman Mentimun (Cucumis sativus L.) Menggunakan Software Plantix di Kabupaten Kampar Provinsi Riau - Mulyadi, Dedi; Ibrahim, Roy; Elfianis, Rita (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to identify the causes of disease and disease symptoms using plantix software, and to determine the incidence of disease and disease resistance that infect cucumber plants in Kampar Regency. This study used a survey method with direct observation in 3 locations and the data obtained in the field were disease symptoms, the number of affected plants, the percentage and intensity of disease attack. Data analysis was carried out at the Laboratory of Plant Disease, Faculty of Agriculture, Riau University. The results showed that (1) the results of identification carried out using Plantix software found that the pathogen that infects cucumber plants in Kampar Regency is Cucumber green mottle mosaic virus (CGMMV) with symptoms of light green or yellow spots and veins clearly visible on young leaves, yellowing leaves, wrinkles, and changes in shape, plant growth is inhibited, the fruit has spots, stripes or a distorted shape (malformation). (2) The highest disease incidence was found in Kampar Subdistrict, 71.16% with disease intensity of 46.95%, followed by Mine Subdistrict with disease incidence of 55.45% and disease intensity of 34.07%, while disease incidence in North Kampar Subdistrict was 37.25% with disease intensity of 18.79%.